Si : X+x-1=3 ; calcule el valor de√(x^2+x^(-2)-3)
solange3009:
el -3 es potencia tambien?
Respuestas
Respuesta dada por:
0
2x=3+1
x=4/2
x=2
[/tex] \sqrt{ x^{2} + x^{-2}-3 } [/tex]
[/tex] \sqrt{2^{2}+ 2^{-2}-3 } [/tex]
![\sqrt{1+ \frac{1}{4} } \sqrt{1+ \frac{1}{4} }](https://tex.z-dn.net/?f=+%5Csqrt%7B1%2B+%5Cfrac%7B1%7D%7B4%7D+%7D+)
![\sqrt{4+ \frac{1}{4}-3 }
\sqrt{4+ \frac{1}{4}-3 }](https://tex.z-dn.net/?f=+%5Csqrt%7B4%2B+%5Cfrac%7B1%7D%7B4%7D-3+%7D+%0A)
![\sqrt{ \frac{5}{4} } \sqrt{ \frac{5}{4} }](https://tex.z-dn.net/?f=+%5Csqrt%7B+%5Cfrac%7B5%7D%7B4%7D+%7D+)
![\frac{ \sqrt{5} }{2} \frac{ \sqrt{5} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7B5%7D+%7D%7B2%7D+)
x=4/2
x=2
[/tex] \sqrt{ x^{2} + x^{-2}-3 } [/tex]
[/tex] \sqrt{2^{2}+ 2^{-2}-3 } [/tex]
Respuesta dada por:
0
2x=4 por lo tanto x=2
√(x^2+x^(-2)-3)
√(x^2+x^6)
x^2/2+x^6/2
x + x^3 = 2 + 2^3= 10
√(x^2+x^(-2)-3)
√(x^2+x^6)
x^2/2+x^6/2
x + x^3 = 2 + 2^3= 10
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años